So, since we have a cubic equation with 4 terms, the first thing we should try is factoring by grouping, so:
![12x^3+2x^2-30x+5 =0 \implies \\ 2x^2(6x+1)-5(6x+1)=0 \implies \\ (2x^2-5)(6x+1) = 0](https://tex.z-dn.net/?f=%2012x%5E3%2B2x%5E2-30x%2B5%20%3D0%20%5Cimplies%20%5C%5C%202x%5E2%286x%2B1%29-5%286x%2B1%29%3D0%20%5Cimplies%20%5C%5C%20%282x%5E2-5%29%286x%2B1%29%20%3D%200%20)
Now that we've factored our equation, we can use ZPP and break it up:
![2x^2-5 = 0 \implies \\ 2x^2=5 \implies\\ x^2=\frac{5}{2} \implies\\ x=\pm\frac{\sqrt{5}}{\sqrt{2}}=\pm\frac{\sqrt{10}}{2} \\ \\ 6x+1 =0 \implies \\ 6x=-1 \implies\\ x=\frac{-1}{6}](https://tex.z-dn.net/?f=%202x%5E2-5%20%3D%200%20%5Cimplies%20%5C%5C%202x%5E2%3D5%20%5Cimplies%5C%5C%20x%5E2%3D%5Cfrac%7B5%7D%7B2%7D%20%5Cimplies%5C%5C%20x%3D%5Cpm%5Cfrac%7B%5Csqrt%7B5%7D%7D%7B%5Csqrt%7B2%7D%7D%3D%5Cpm%5Cfrac%7B%5Csqrt%7B10%7D%7D%7B2%7D%20%5C%5C%20%5C%5C%206x%2B1%20%3D0%20%5Cimplies%20%5C%5C%206x%3D-1%20%5Cimplies%5C%5C%20x%3D%5Cfrac%7B-1%7D%7B6%7D%20%20)
So, our solutions are:
![x\in \{\frac{\sqrt{10}}{2},-\frac{\sqrt{10}}{2},-\frac{1}{6}\}](https://tex.z-dn.net/?f=%20x%5Cin%20%5C%7B%5Cfrac%7B%5Csqrt%7B10%7D%7D%7B2%7D%2C-%5Cfrac%7B%5Csqrt%7B10%7D%7D%7B2%7D%2C-%5Cfrac%7B1%7D%7B6%7D%5C%7D%20)
Answer:
![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
Step-by-step explanation:
We will be using 2 properties of radicals in this simplification (outlined below).
<em>Let's simplify this:</em>
![2\sqrt{27} +\sqrt{12} -3\sqrt{3}-2\sqrt{12}\\ =2\sqrt{9*3}+\sqrt{4*3} -3\sqrt{3}-2\sqrt{4*3} \\=2\sqrt{9} \sqrt{3} +\sqrt{4} \sqrt{3}-3\sqrt{3}-2\sqrt{4} \sqrt{3} \\=2(3)\sqrt{3}+(2)\sqrt{3} -3\sqrt{3}-2(2)\sqrt{3} \\ =6\sqrt{3} +2\sqrt{3}-3\sqrt{3}-4\sqrt{3} \\=\sqrt{3}](https://tex.z-dn.net/?f=2%5Csqrt%7B27%7D%20%2B%5Csqrt%7B12%7D%20-3%5Csqrt%7B3%7D-2%5Csqrt%7B12%7D%5C%5C%20%3D2%5Csqrt%7B9%2A3%7D%2B%5Csqrt%7B4%2A3%7D%20-3%5Csqrt%7B3%7D-2%5Csqrt%7B4%2A3%7D%20%5C%5C%3D2%5Csqrt%7B9%7D%20%5Csqrt%7B3%7D%20%2B%5Csqrt%7B4%7D%20%5Csqrt%7B3%7D-3%5Csqrt%7B3%7D-2%5Csqrt%7B4%7D%20%5Csqrt%7B3%7D%20%5C%5C%3D2%283%29%5Csqrt%7B3%7D%2B%282%29%5Csqrt%7B3%7D%20-3%5Csqrt%7B3%7D-2%282%29%5Csqrt%7B3%7D%20%5C%5C%20%3D6%5Csqrt%7B3%7D%20%2B2%5Csqrt%7B3%7D-3%5Csqrt%7B3%7D-4%5Csqrt%7B3%7D%20%20%5C%5C%3D%5Csqrt%7B3%7D)
First answer choice is right.
Answer:
x = -1,5
Step-by-step explanation:
2x² - 8x - 10
2x² - 10x + 2x - 10
2x(x - 5) + 2(x - 5)
(x - 5)(2x + 2)
x = 5 x = -2/2
x = -1,5